Особливості компоновки муфт з торцевою установкою канатів тангенціального розташування - Проценко, Владислав Олександрович; Клементьева, Оксана Юріївна (НТУ "ХПІ", 2016)
В статті представлені дослідження впливу компоновочних параметрів муфт з торцевою установкою канатів тангенціального розташування на умови їх геометричного існування. В результаті виконання досліджень розкрито цей вплив та отримано математичні вирази для використання при проектувальному розрахунку муфт під час перевірки основних умов їх геометричного існування. Розглянуто умови відсутності інтерференції втулок зовнішньої та внутрішньої напівмуфт, а також умови відсутності інтерференції канатів та суміжних втулок внутрішньої напівмуфти. Отримані залежності апробовані при проектуванні муфти, а результати розрахунку за ними перевірені порівнянням із результатами побудови і показали співпадіння. Отримані результати можуть бути використані при проектуванні муфт з торцевою установкою прямих канатів тангенціального розташування.

Most of the parts and units of machines is a complex design, convenient design which is possible only after a detailed study of the processes occurring in them during the work, as well as development on the basis of these new methods of knowledge of their design. Moreover, for many of the rational design of assembly units is the result of a series of calculations performed by the method of successive approximations. An example is the layout calculations for refinement such as gears in preassigned dimensions. They are no exception and flexible couplings. Among the couplings among the most promising designs are couplings with rope elastic elements. In previous work, the authors proposed the design of couplings with rope end units elastic elements chordal and tangential arrangement. Today justified some parameters such couplings, which at the same time is not enough to create a methodology for their design. The paper presents the study of the effect of layout parameters coupling with the end of the tangential location of the installation of ropes on the conditions of geometric existence. Arrangement considered limiting geometric nature that must be considered when designing joints. These conditions take into account the possibility of tightening fasteners, bushings opportunity neighborhood inner coupling halves, the possibility of relative rotation of the coupling halves, the lack of interference of the outer and inner sleeves of the coupling halves, the absence of interference of adjacent ropes and sleeves inner halfcoupling. As a result of research obtained mathematical expressions to be used in the calculation of engineering couplings checking the basic conditions of their geometric existence. These have been tested according to the design of the coupling, and the calculation results are checked by comparing them with the results of construction and found a match. The results can be used in the design of the coupling with the end of direct installation of ropes tangential location.
Features layout with face couplings installing ropes tangential location
Keywords: навантаження; зазор; компоновочні параметри; проектувальний розрахунок муфт; gap; torque